2017
DOI: 10.2147/amep.s138557
|View full text |Cite
|
Sign up to set email alerts
|

Predicting United States Medical Licensure Examination Step 2 clinical knowledge scores from previous academic indicators

Abstract: The use of multiple academic indicators to identify students at risk of experiencing difficulty completing licensure requirements provides an opportunity to increase support services prior to high-stakes licensure examinations, including the United States Medical Licensure Examination (USMLE) Step 2 clinical knowledge (CK). Step 2 CK is becoming increasingly important in decision-making by residency directors because of increasing undergraduate medical enrollment and limited available residency vacancies. We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 10 publications
4
11
0
1
Order By: Relevance
“…There was also a significant correlation between the scores in the USMLE Step 1 and USMLE Step 2 CK. This correlation supports prior work done by Monteiro et al,18 who reported that the USMLE Step 1 is a significant predictor of the USMLE Step 2 CK score.…”
Section: Discussionsupporting
confidence: 90%
“…There was also a significant correlation between the scores in the USMLE Step 1 and USMLE Step 2 CK. This correlation supports prior work done by Monteiro et al,18 who reported that the USMLE Step 1 is a significant predictor of the USMLE Step 2 CK score.…”
Section: Discussionsupporting
confidence: 90%
“…For example, score and number of attempts at Part B MRCS were found to be significant independent predictors of both selection into higher surgical training (HST, year 3 onwards of training) and performance during HST 3,6 . Similar relationships have been observed between the written papers and clinical exams of the equivalent physician examination in the UK, the Membership of the Royal College of Physicians (MRCP), and for the Medical Licensing Examination ® (USMLE ® ) in the USA 7,8 . Performance at the USMLE ® has also been found consistently to predict performance in the American Board of Surgery Qualifying and Certifying Examinations 9,10 , and may explain why US surgical training directors rank USMLE ® performance as one of the most important factors in selecting applicants for surgical training 11 .…”
Section: Introductionsupporting
confidence: 58%
“…Information about students’ medical knowledge achievement will still be needed and could be captured more flexibly through confirmation of minimum competence on clerkship examinations or one but not necessarily both of the Step examinations before residency, given the high correlation among scores on these examinations. 17 …”
Section: Broadening the Assessment Toolboxmentioning
confidence: 99%